دور حوكمة الشركات في تحقيق كفاءة وفعالية سوق الأوراق المالية - جريو كلتوم (جامعة البليدة2-كلية العلوم الإقتصادية والعلوم التجاريةوعلوم التسيير, 2019)
الملخص: تهدف هذه الدراسة إلى إبراز الدور الذي تساهم به حوكمة الشركات في تحقيق كفاءة سوق الأوراق المالية وإظهار طبيعة العلاقة بين هذين المتغيرين. وتمثلت عينة الدراسة في سوق مصر للأوراق المالية، سوق الإمارات للأوراق المالية، وكذا سوق الجزائر للأوراق المالية خلال الفترة الممتدة من سنة 2006 إلى غاية سنة 2016. وقد تم الاعتماد على المنهج الاستنباطي بأداتيه الوصف والتحليل، وهذا من خلال تقديم المفاهيم المتعلقة بحوكمة الشركات ومبادئها الصادرة عن مختلف الهيئات الدولية، وعرض الإطار العام لسوق الأوراق المالية وكفاءتها ومختلف مستوياتها، مع تحليل لدور مبادئ حوكمة الشركات في تحسين كفاءة سوق الأوراق المالية. بالإضافة إلى تقديم وصف وتحليل لواقع ومساهمة حوكمة الشركات في رفع كفاءة سوق الأوراق المالية في كل من مصر والإمارات، كما تم توظيف ذات المنهج في دراسة حالة سوق الأوراق المالية الجزائرية. وقد توصلت الدراسة إلى أن لحوكمة الشركات دوراً فعالاً في رفع وتحسين كفاءة سوق الأوراق المالية؛ فالتزام الشركات بتطبيق مبادئ الحوكمة سيؤدي إلى تطوير الإفصاح والشفافية وسلامة البيانات المفصح عنها في القوائم المالية، وبالتالي تعزيز ثقة المستثمرين وزيادة جاذبية سوق الأوراق المالية، الأمر الذي يجعلها تصل إلى السعر العادل للأوراق المالية وبالتالي تحقيق كفاءة سوق الأوراق المالية. الكلمات المفتاحية: حوكمة الشركات، سوق الأوراق المالية، كفاءة سوق الأوراق المالية.This study aims to highlight the role that corporate governance contributes to achieving the efficiency of the stock market and to show the nature of the relationship between these two variables, The sample of the study was in the Egyptian Stock Exchange, the Emirates Securities Market and the Algerian Stock Exchange during the period from 2006 to 2017. The methodology was based on descriptive and analytical tools, and this was achieved by presenting concepts related to corporate governance and principles issued by various international bodies, And presented the general framework of the stock market and efficiency and various levels, With an analysis of the role of the principles of corporate governance in improving the efficiency of the stock market, in addition to providing a description and analysis of the reality and contribution of corporate governance in rising the efficiency of the stock market in Egypt and the UAE, The same methodology was used in the study of the state of the Algerian stock market. The results of this study showed that corporate governance has an effective role in rising and improving the efficiency of the stock market, The commitment of companies to implement the principles of governance will lead to the development of disclosure and transparency and the integrity of the data disclosed in the financial statements and thus enhance the confidence of investors and increase the attractiveness of the stock market, which makes them up to the fair price of securities and thus achieve the competence of the stock market. Keywords: Corporate Governance, Stock Market, Stock Market competence
دراسة تحليلية تقويمية لحالة بورصة الجزائر
Keywords: حوكمة الشركات; سوق الأوراق المالية; كفاءة سوق الأوراق المالية; بورصة الجزائر; تحقيق كفاءة